Cow Manure Application Cuts Chemical Phosphorus Fertilizer Need in Silage Rice in Japan - Thanh Tung Nguyen; Yuka Sasaki; Mitsuhiko Katahira; Dhirendranath Singh (Agronomy, 2021)
Cow manure is a good source of phosphorus (P). Here, we investigated whether the amount of P fertilizer can be reduced when cow manure is applied to paddy soil based on growth, P uptake, yield, and soil P status evaluation. Treatments included unfertilized control (CK); manure plus chemical nitrogen (N), potassium (K), and P fertilizer (MNK P); MNK and 75% P (MNK ¾ P); MNK and 50% P (MNK ½ P); MNK and 25% P (MNK ¼ P); and MNK. Manure was applied at the rate of 10 t ha−1 in fresh weight base. The P fertilizer was applied at 34.9 kg P ha−1 as full dose. Treatment with MNK resulted in the same growth, P uptake, and yield as that with the P fertilizer. P uptake and yield did not respond to P input from chemical fertilizer owing to high soil Olsen P levels. Moreover, MNK could maintain soil Olsen P and total P. Manure application resulted in a positive partial P balance. These results suggest that manure application can cut P fertilizer requirements in P-rich soils, while maintaining soil P for optimal rice growth and yield. By using cow manure in rice production, farmers can conserve finite P resources.